EFFECT OF LENGTH OF PREMATURE RUPTURE OF MEMBRANES PERIOD TOWARD APGAR SCORE OF THE INFANT AND MATERNAL LEUKOCYTE SERUM IN ULIN GENERAL HOSPITAL BANJARMASIN - Yosef Dwi Cahyadi Salan (Berkala Kedokteran, 2017)
Abstract: Premature rupture of membranes (PROM) is a condition of rupture of membranes before the birth takes place. The incidence of PROM varies from 3% to 10% of all births and complicates more than 3% of pregnancies with PROM. The purpose of this study was to determine the relationship between the length of the PROM period toward the APGAR score of the infant and maternal leukocyte serum. The research design was analytic observational with retrospective cohort approach. From the result we found a correlation between PROM period with outcome of infant’s APGAR score, there were a total of 89 samples fulfilling the inclusion criteria, with 57 samples of PROM<12 hours (51 with good APGAR score and 6 with bad APGAR score) and 32 samples PROM> 12 hours (16 with good APGAR score, and 16 with bad APGAR score). From the result of the correlation of leukocyte level with the length of PROM period was found total of 84 samples fulfilling the inclusion criteria, with 54 samples of PROM<12 hours (53 with normal leukocyte score and 1 with leukocytosis score) and 30 samples PROM> 12 hours (28 with normal leukocyte score, and 2 with leukocytosis score). From the analysis results we obtained a strong relationship between the length of PROM period with the infant’s APGAR (P = 0.0001, OR 8.5), whereas in the relationship between the length of PROM period with maternal blood leukocyte level there is no significant relationship (p= 0,599).  Keywords: Premature Rupture of Membranes, APGAR, Leukocyte Serum